The natural history of multiple sclerosis: a geographically based study 9: observations on the progressive phase of the disease. - Kremenchutzky, M; Rice, G; Baskerville, J; Wingerchuk, D; Ebers, G (2006)
The clinical features of relapses and progression largely define multiple sclerosis phenotypes. A relapsing course is followed by chronic progression in some 80% of cases within 2 decades. The relationship between these phases and long-term outcome remains uncertain. We have analysed these clinical features within a well-studied natural history cohort with mean follow-up of 25 years. For the entire cohort, median times to reach Disability Status Scale (DSS) 6, 8 and 10 were 12.7, 20.6 and 43.9 years, respectively. Among 824 attack-onset patients, the great majority entered a progressive phase with a mean time to progression of 10.4 years. The effects of relapses often cloud the clinical onset of progression. However, there are circumstances where onset of progression is early, relatively discrete and identifiable at DSS of 2 or less. Three subgroups allow for clarity of outcome comparison and they are (i) cases of primary progressive (PP) disease, (ii) attack-onset disease where only a single attack has occurred before onset of progression (SAP) and (iii) secondary progressive (SP) disease where recovery from relapses allows recognition of the earliest clinical stages when progression begins. Here we compare survival curves in these three groups. Among cohorts of SAP (n = 140), PP (n = 219) and SP (n = 146) where progression was stratified by DSS at its onset, there was no difference in time to DSS 6, 8 and 10. These findings demonstrate that the progressive course is independent of relapses either preceding the onset of relapse-free progression or subsequent to it. Among SAP patients, the degree of recovery from the single defining exacerbation had no significant effect on outcome. The site of the original attack was not usually where progression began. The relatively stereotyped nature of the progressive phase seen in all progressive phenotypes suggests regional and/or functional differential susceptibility to a process that appears degenerative in nature. The highly prevalent distal corticospinal tract dysfunction in progressive disease and the pathologically demonstrated selective axonal loss seen in this tract raises the possibility of a dying back central axonopathy, at least in part independent of plaque location or burden. Despite considerable individual variation, the progressive course of disability seen in groups of PP, SAP and SP-DSS2 is similarly stereotyped in quality and pace and may entail mechanisms common to all forms of progressive multiple sclerosis. The possibility that this is the primary process in some cases must be considered.